The Swaying Ship of Men's Politics: A Metaphor Analysis - Kastein, Mara (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2021)
In this article, I examine the metaphors of equality-oriented men's politics as a form of discursive practices. In my dissertation research, I used metaphor analysis to supplement grounded theory methodology and discourse analysis to enhance the results. In doing so, the metaphor of equality-oriented men's politics is depicted as unstable, wavering, balancing, and discordant, for it is imagined as a swaying ship rocking on the sea without a fixed route. The sea is society or the overarching politics of equality. This is conceived as unpredictable and capricious, putting equality-oriented men's politics appear at its mercy.